High-Temperature Reactor Cleaning Using Chlorine Trifluoride Gas for Silicon Carbide Chemical Vapor Deposition. (1st January 2019) - Kurashima, Keisuke; Hayashi, Masaya; Habuka, Hitoshi; Ito, Hideki; Mitani, Sin-ichi; Mizushima, Ichiro; Takahashi, Yoshinao
Abstract : The high-temperature cleaning of a silicon carbide chemical vapor deposition reactor was developed using chlorine trifluoride gas and purified pyrolytic carbon (PyC) as the susceptor coating material. The purified PyC could be exposed to the chlorine trifluoride gas without causing serious damage at temperatures up to 570°C, which was in the range providing a sufficiently high silicon carbide etching rate. The spontaneous temperature increase at the susceptor surface due to the exothermic reaction heat was moderated by means of adding nitrogen gas. Thus, the particle-type silicon carbide layer could be cleaned while preventing peeling of the purified PyC surface and obtaining a practical etching rate. Additionally, the peeled surface of the purified PyC could be recovered by annealing at 900°C in ambient nitrogen containing oxygen.